2016
DOI: 10.1016/j.ejon.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in fatigue, decrements in energy, and sleep disturbance in oncology patients receiving chemotherapy

Abstract: Objective The number of older adults with cancer is increasing. Given the limited amount of research and the inconsistent findings regarding age differences in common physical symptoms associated with cancer and its treatments, the purposes of this study, in a sample of oncology outpatients receiving chemotherapy (CTX), were to evaluate for age differences in demographic and clinical characteristics, as well as in occurrence rates of and severity ratings for fatigue, decrements in energy, and sleep disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…[1] Fatigue negatively impacts patients’ daily activities and their quality of life (QOL). [2] While a growing body of evidence suggests that average fatigue severity is associated with a number of demographic and clinical characteristics,[310] these studies did not evaluate diurnal variations in fatigue severity. Recent work by our research team [1114] and others [1517] found that fatigue severity is extremely variable over the course of a day and among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Fatigue negatively impacts patients’ daily activities and their quality of life (QOL). [2] While a growing body of evidence suggests that average fatigue severity is associated with a number of demographic and clinical characteristics,[310] these studies did not evaluate diurnal variations in fatigue severity. Recent work by our research team [1114] and others [1517] found that fatigue severity is extremely variable over the course of a day and among individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of chemotherapy on sleep quality has been well documented in patients with cancer (Bischel et al, ; Hong et al, ). Palesh et al () concluded that the rate of sleep disturbance was three times higher in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence showed that patients with cancer could have decreased sleep time and sleep efficiency (Daniel et al, 2016). In previous studies, persistent insomnia symptoms were reported to occur in as many as 22%-28% of long-term paediatric cancer survivors (Daniel et al, 2016;Zhou, Manley, Marcus, & Recklitis, 2016 The effect of chemotherapy on sleep quality has been well documented in patients with cancer (Bischel et al, 2016;Hong et al, 2014). Palesh et al (2010) concluded that the rate of sleep disturbance was three times higher in patients receiving chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient characteristics may also be associated with sleep disturbance in patients with cancer. Younger age has been associated with increased sleep disturbance [15,[22][23][24], although other studies have found no association between age and sleep disturbance in patients with breast cancer [1]. Additionally, a large (n=12,098) longitudinal study found that breast cancer diagnosis was not signi cantly related to decreased sleep quality compared to pre-diagnosis, although sleep quality continued to decrease over time [25].…”
Section: Introductionmentioning
confidence: 98%